Etika Islam pada Bisnis Biro Travel Haji dan Umrah dalam menarik minat jamaah di Tareem Tour Purwokerto - Novi Nur Aini; Amirotun Solikhah (GREAT: Jurnal Manajemen dan Bisnis Islam, 2026)
This study aims to analyze the implementation of Islamic business ethics in the practices of a Hajj and Umrah travel agency and its influence on attracting pilgrims’ interest at Tareem Tour Purwokerto. Using a qualitative descriptive approach, the analysis is grounded in the principles of Islamic business ethics, namely shiddiq (honesty), amanah (trustworthiness), tabligh (transparent communication), and ‘adl (justice). The findings reveal that transparent package information, accountable financial management, ethical digital marketing communication, and fair service delivery significantly contribute to building pilgrims’ trust. The integration of ethical values with sharia marketing strategies strengthens institutional branding and enhances customer loyalty through social recommendations. The study concludes that Islamic ethics function not merely as moral obligations but also as a competitive strategic framework within the increasingly dynamic Hajj and Umrah travel industry. The success of Tareem Tour Purwokerto in attracting pilgrims is closely linked to its consistent application of Islamic ethical values across its business operations.